Srategic change and transformation: A case study at Malaysian Banking Berhad (Maybank) - Ahmad, Hartini; Mohtar, Shahimi; Ahmad Arshad, Darwina; Mustapa, Azrain Nasyrah (Universiti Utara Malaysia, 2012)
Nowadays, the challenges faced by the banking industry are very huge because most banks emerged from a period dominated by cost-cutting, downsizing or downscaling.This case study aims to analyse the external and internal factors of Maybank Berhad by looking at products and service marketing strategic, and transformation program that had took place in this company.In line with “Community Financial Services and Global based Banking” strategic thrusts, numerous transformation strategy successfully implemented, i.e., Insurance & Takaful, Information Technology Transformation Programme and Quality of Service. Three of these strategies closely related to staff and customers of Maybank.It is very crucial for the company to understand customer expectations and perceptions of offered quality.This is because the perceived level of satisfaction by a customer is a key to maintain customer loyalty as well as uphold an image of the banking industry as the best industry in the world in a very competitive environment.In addition, various internal and external analyses were performed towards Maybank, such as PESTEL analysis, Porter's Five Forces, and VRIO analysis.The results showed that many initiatives done by Maybank align with the vision and mission, have quick wins; short and medium-term strategies, and long-term strategies.The initiatives done focused on the human resources as well as the company strategies as a whole.Furthermore, several comments and suggestions have been presented to Maybank in order to ensure how the company can become better.